THE ANTECEDENTS AND CONSEQUENCES OF BRAND LOVE: A RESEARCH ON THE RAY-BAN BRAND (Third Sector Social Economic Review, 2024)
Consumers form connections with brans not only as participants in buying or exchanges but also view brands as an extension of themselves through the emotional, cognitive, and behavioural connections they build with brands. Therefore, the connections formed between consumers and brands play a crucial role in shaping consumers' perceptions towards brands in the modern world. In this sense, the study examines the effects of brand identification, brand coolness and brand love on consumers' purchase and willingness to pay more intentions within the scope of symbolic self-completion theory. These notions have been widely recognised as contemporary and relevant in the academic marketing literature in recent years. Within this particular framework, a comprehensive examination was conducted using a sample size of 253 surveys comprising individuals aged 18 and above who possess knowledge of the Ray-Ban Sunglasses brand. The research findings indicate that all hypotheses have been confirmed. Research findings suggest that brand identification positively impacts consumers' perception of brand coolness. It is revealed that brand coolness has a positive effect on brand love, and brand love has a positive effect on consumers' intention to purchase the brand and their intention to pay more for the brand.
Keywords: Brand Love; Brand Coolness; Brand Identification; Intention to Pay More; Symbolic Self-Completion Theory